(untitled) (Medico Legal Update, 2021)
Pseudomonas aeruginosa have ability to form biofilm, this biofilm responsible for wide infections and antibiotic resistance development. A novel mechanism to antibiotic resistance mechanisms utilized by biofilm represented by the presence of ndvB geneencodes a glucosyltransferase enzyme involved in the formation of this glucans, thisglucan mediated sequestration antibiotic away from their cellular targets. In this study was collected 145 samples from burns patients and identification by biochwmicaltsets and Vitek-2 compact. The studied the biofilm formation was measured using micro titer plate method we found that 49 isolates (100%) of P.aeruginosa were biofilm positive and measured minimal biofilm inhibitory concentration(MBIC) of biofilm P.aeruginosa positive biofilmused cefepime as antibiotic was tested using microtiter plate microdilution method (MBIC) values (1gm/ml).Molecular detection of ndvB gene was measured using PCR 100% of isolates were found to contain ndv B gene. Expression of ndvB gene was significantly high in biofilm isolates using sub- MBIC values of cefepime. Expression of ndvB gene was significantly high in biofilm isolates using glucose with concentration 1% and 2%. This study we concluded biofilm formation is an important trait of P.aeruginosa that isa cause of antibiotic resistance. ndvB gene expression responsible for the biofilm resistance mechanism in P. aeruginosa biofilms.